2018
DOI: 10.1002/chem.201804987
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Editing of Callyspongiolide, Part 1: The Alkyne Metathesis/trans‐Reduction Strategy

Abstract: A path‐scouting investigation into the highly cytotoxic marine macrolide callyspongiolide is reported that capitalizes on the selective formation of the C10−C11 alkene site. While the closure of the macrocycle by ring closing alkyne metathesis (RCAM) with the aid of a molybdenum alkylidyne complex was high yielding, the envisaged semi‐reduction of the cycloalkyne to the corresponding E‐alkene proved challenging. The reasons are likely steric in origin, in that the methyl branches on either side of the alkyne s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 107 publications
1
30
0
Order By: Relevance
“…The required aldehyde partner was attained by adaptation of a fragment synthesis described in the accompanying paper . To this end, the readily available butyrolactone derivative 12 was subjected to Stahl oxidation and the resulting aldehyde transformed into dibromoolefin 13 by standard means (Scheme ) .…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The required aldehyde partner was attained by adaptation of a fragment synthesis described in the accompanying paper . To this end, the readily available butyrolactone derivative 12 was subjected to Stahl oxidation and the resulting aldehyde transformed into dibromoolefin 13 by standard means (Scheme ) .…”
Section: Resultsmentioning
confidence: 52%
“…With a robust access to 20 secured, the total synthesis of callyspongiolide was completed by cleavage of the remaining TBS‐ether and installation of the conspicuous carbamate functionality . In the final step the side chain was attached via Sonogashira coupling of 21 with alkyne 24 , for which an efficient asymmetric synthesis is outlined in the accompanying paper . The analytical and spectral data of our synthetic samples of callyspongiolide were in excellent accord with those reported in the literature, except that we had been misled at the outset of our project by the mis‐assigned absolute configuration in the original report to pursue the non‐natural enantiomer ent ‐ 1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the point where our numerous attempts at synthesizing the macrocyclic portion of rhizoxin F ( 2 ) by means of RCM/RRCM had all met with failure, we felt that a radical change in strategy was necessary. Triggered by Fürstner’s groundbreaking work on RCAM in the field of natural product synthesis (for early examples, see in [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]; for more recent examples, see in [ 23 , 79 , 80 , 81 ], we reasoned that this method would be a promising alternative to RCM. (For a review on the use of RCAM in natural product synthesis, see in [ 82 ].)…”
Section: Resultsmentioning
confidence: 99%
“…Further total syntheses of (+)-callyspongiolide (1 a) by Fürstner et al [24,25] and the natural enantiomer (À )-callyspongiolide (2) by Harran et al [26] and S. Ghosh et al [27] were reported in 2018. Partial syntheses of this natural product have also been reported, with the synthesis of the macrocyclic core of (+)-callyspongiolide (1 a) by S. Ghosh [28] and the synthesis of the unsaturated side-chain of (À )-callyspongiolide (2) by Kotora [29] both reported in 2016, and a further synthesis of C3-C15 fragment of the macrocyclic core of (+)-callyspongiolide (1 a) published by Mohapatra in 2018.…”
Section: Introductionmentioning
confidence: 99%